Grapho-analytic method of determining the minimum groove at the pivot root of symmetrical switches (Transport systems and technologies, 2023)
Switches are a barrier place in the track for setting the permissible speeds for trains on the main tracks, as they have special structural devices for branching traffic from the main track to the secondary track. Symmetrical switches have a number of advantages compared to conventional ones: with the same brand with conventional switches, symmetric ones allow significantly higher speeds for the train movement with side tracks; symmetrical switches have a shorter length with the same radii of the transfer curves; it is possible to apply crosspieces with a larger angle than in the conventional switches while preserving the length of the curve and the radius. The specified qualities of single, versatile, symmetrical switches determined their use scope. On the main transport tracks, symmetrical switches are used in sorting parks of the stations, as well as in main tracks when it is necessary to achieve increased speeds of movement on both side tracks. Symmetric switches according to the purpose and design have the significant differences from the most conventional switches, and therefore the study of these designs is important and relevant. Moreover, very few scientific works were devoted to such studies of Ukrainian railways.
Keywords: symmetric switches, design, minimum groove between the pivot and the frame rail.